RAPS: PROS AND CONS - Поліщук, А. А.; Булавкіна, Т. П. (Scientific Progress & Innovations, 2014)
The results of the analysis of literature and information sources from use in livestock feeding rapeseed and its products - meal, meal and vegetable oil - today. Determined their positive and negative sides. Found that feeding animals can be used as rapeseed and its products (meal, rapeseed meal and oil). Harmful substances in rapeseed - glucosinolates and erucic acid - limiting the widespread use of rape feeds in animal nutrition. The level of these substances in the seeds varies widely and depends on the type of rape. Canola (00) spring rapeseed varieties do not contain antinutrient substances. Rape animal feed fed in limited quantities and only in the composition of the feed.